The Mu‘tazilah School: History, Key Figures, and Core Doctrines in the Perspective of Islamic Rationalism - Irmawati I; Indo Santalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Muâ€˜tazilah school represents one of the most significant rationalist theological movements in the history of Islamic thought. Emerging in the 8th century CE in Basra, it was pioneered by WÄá¹£il ibn â€˜Aá¹Äâ€™ as a response to theological debates concerning the status of grave sinners and as an effort to uphold the principles of divine unity and justice through reason. This study aims to examine the historical emergence, major figures, and fundamental doctrines of Muâ€˜tazilah, known collectively as Uá¹£Å«l al-Khamsah (The Five Principles). Employing a qualitative approach with a library research method, the study explores both classical and modern sources on Islamic theology (kalÄm) and philosophy. The findings indicate that the Muâ€˜tazilah positioned reason (â€˜aql) alongside revelation as a primary means for understanding religious teachings. Its five foundational principles include at-Tawá¸¥Ä«d (the Oneness of God), al-â€˜Adl (Divine Justice), al-Waâ€˜d wa al-Waâ€˜Ä«d (Promise and Threat), al-Manzilah bayna al-Manzilatayn (the Intermediate Position), and al-Amr bi al-Maâ€˜rÅ«f wa an-Nahy â€˜an al-Munkar (Commanding Good and Forbidding Evil). Through these doctrines, Muâ€˜tazilah emphasized human freedom, moral responsibility, and rational interpretation of religious texts. The existence of this school contributed significantly to the development of Islamic theology (â€˜ilm al-kalÄm) and philosophy, particularly during the reign of Caliph al-Maâ€™mÅ«n of the Abbasid dynasty. Although its influence declined with the rise of Ashâ€˜arism, the intellectual legacy of Muâ€˜tazilah endures within modern Islamic rationalism. Thus, Muâ€˜tazilah stands not only as a symbol of classical Islamic intellectual awakening but also as enduring evidence that Islam possesses a profound tradition of critical and rational thought.